Phytoseiid mites of the genus Neoseiulus hughes (Acari: Phytoseiidae) from subSaharan Africa - Zannou, I.; Moraes, G.J. de; Ueckermann, E.A.; Oliveira, A.; Yaninek, John S.; Hanna, R. (2006)
Thirty phytoseiid mite species of the genus Neoseiulus Hughes are reported from sub-Saharan Africa. Ten of these species are described for the first time and 14 nominal species are redescribed. Most of the species were collected from cassava groves in tropical Africa and from other habitats in South Africa. A key is included to distinguish these species and six other species known to occur in the region but not evaluated in this study.